1177 Mentorship for medical students in paediatrics: is it beneficial?. (17th August 2022) - Hulbert, Rebecca; Larsson, Martina; Shad, Nadia; Roueche, Alice; Macaulay, Chloe
Abstract : Aims: Junior doctor mentors are allocated to all fourth year medical students undertaking their Child Health placement at one tertiary Children's Hospital. The scheme aims to complement formal teaching and clinical supervision during their placement. Student engagement in the mentor scheme is encouraged, but not mandatory. The relationship between student and mentor is encouraged to be student-directed to promote focus on individual student's needs. This study aims to assess student and mentor perceptions of the current programme, addressing the following questions: Do students feel that a mentor is useful during clinical placement? What are students' perceived obstacles to engagement in this programme? Do junior doctors feel they benefit from the experience of mentoring? Methods: Two consecutive blocks of students were surveyed using anonymous questionnaires following completion of their Child Health placement during the 2021/22 academic year. Junior doctors who volunteered as mentors over the same periods were also surveyed. Feedback was encouraged from all students and allocated mentors, regardless of engagement with the programme. Results: Responses were received from 24 medical students; 50% reported that they engaged with their mentor during their Child Health placement. The majority of these students met their mentor at least two-three times over the course of their six week clinical placement. Two students met with their mentor over six times during the block. 92% of students who met with their mentor rated this relationship as either 'somewhat beneficial' or 'beneficial'. Students commented that it is a 'great system' and 'the scheme was very useful'. One student requested the scheme be implemented across other placements. Student-reported benefits of the mentor scheme included: 1. Additional clinical teaching 2. Increased confidence 3. Assistance with completion of supervised learning events for their portfolio 4. Access to out of hours experiences and shadowing 5. Careers advice Students who did not meet with their mentor described two key reasons for this: perceived lack of time during placement and a lack of clarity regarding the mentor role. The majority of mentors who met with their allocated students felt that participating in the scheme was beneficial. Mentor-reported benefits included development of leadership, teaching and feedback skills, and a sense of personal satisfaction. Conversely, mentors whose students did not engage with the scheme reported no benefit to themselves, with one reporting this experience was 'deflating'. Conclusion: Medical students report that engagement with an allocated junior doctor mentor during their Child Health placement is beneficial to them. Junior doctor mentors also find their role to be largely positive, however lack of engagement from the students can have undesired negative impact. A key obstacle to engagement in the scheme was a lack of clarity regarding the mentor role; this may suggest the concept of mentorship is unfamiliar to medical students. Despite this, positive feedback regarding the concept of the scheme and the self-reported benefits suggest that mentorship is valuable to medical students on clinical placement. We plan to further develop this scheme by increasing student awareness of the mentor role and providing additional support and training to the junior doctor mentors.